EndoTHeF: Endoluminal Treatment of Hemorrhoids with Foam - Maurizio Ronconi (Shiraz University of Medical Sciences, 2018)
Background: Hemorrhoids are normal anatomical structures, present in individuals from birthandrecognisable even in intrauterinelife. When we talk about haemorrhoids in actual fact we refer to the symptoms caused by haemorrhoids. Currently surgery isconsidered the gold standard in the treatment of hemorrhoids.Objectives: In our work we propose the application of an alternative, outpatient and painless treatment of hemorrhoids usingintraluminal injection of sclerosing foam (EndoTHeF), demonstrating the safety and feseability of this procedure.Methods:We enrolled 615 patients frommay 2008 to september 2018 with proctorragy from second and third degree hemorrhoids.Regular 3-week control examinations for all patients were scheduled. A total of 1427 procedures were carried out, with an average of2.32 sessions per patient.Results: Four hundred seventy six patients were available for follow-up, which lasted on average 12 months. In 83% of the casesproctorragy disappeared as early as after the first session. The analysis of a validity score concerning bleeding, pain level and senseof discomfort reported by patients showed a statistically significant difference (P < 0.0015) between before and after procedure.Conclusions: Hemorrhoidal endosclerosis with foam seems to be an effective and safe method to cure hemorrhoidal pathologiesand seems to offer good results in the short-middle term with acceptable results in terms of patient comfort and overall cost tosociety.